Changes in UK renal oncological surgical practice from 2008 to 2017: implications for cancer service provision and surgical training. (12th January 2021) - Devlin, Conor M.; Fowler, Sarah; Biyani, Chandra Shekhar; Forster, James A.
Abstract : Objective: To determine and analyse the temporal changes in oncological nephrectomy practice and training opportunities using data obtained from the UK British Association of Urological Surgeons nephrectomy register from 2008 to 2017. Patient and Methods: All nephrectomies within the dataset for this time period were analysed ( n = 54 251). Cases were divided into radical nephrectomy (RN), partial nephrectomy (PN) and nephroureterectomy (NU). Simple nephrectomy, donor nephrectomy and benign PN were excluded. The annual frequencies for each oncological nephrectomy method, surgical approach, grade of surgeon, hospital caseload numbers and short‐term surgical outcomes were determined. Results: Reported annual nephrectomy numbers increased by 2.5‐fold in the 9‐year time period. The number of hospitals performing nephrectomies decreased by 22%, however, more than 40% of centres performed more than 70 cases a year. There was a trend towards a decrease in overall length of hospital stay (9 vs 5 days; P < 0.01) and decreased transfusion rates. The proportion of minimally invasive procedures increased from 57% to 75%, with nephron‐sparing rates increasing from 8.9% overall to 24.8%. With regard to surgical technique, robot‐assisted surgery saw a mean annual increase of 222%. Overall, there was a 10% decrease in the proportion of PNs performed by trainee surgeons. Conclusions: Renal surgery has changed considerably with regard to volume and also surgical approach, with rates of nephron‐sparing surgery and minimally invasive surgery significantly increasing. Increasing hospital centralization and institutional experience, and a shift to robot‐assisted surgery appear to have contributed to the observed improved patient outcomes. The increasing utilization of robot‐assisted surgery has potential implications and challenges for the training of future urology surgeons.